Image-Guided Radiofrequency Hyperthermia (RFH)-Enhanced Direct Chemotherapy of Hepatic Tumors: The Underlying Biomolecular Mechanisms - Qian, Kun; Chen, Minjiang; Zhang, Feng; Chick, Jeffrey Forris Beecham; Ji, Hongxiu; Zheng, Chuansheng; Yang, Xiaoming (Frontiers in Oncology, 2021)
Radiofrequency ablation (RFA) is currently used as an alternative to treat Hepatocellular carcinoma (HCC) patients, however, there are high local recurrence rate, particularly for tumors beyond 5-cm. Residual tumor cells, particularly at the margins, that may not be completely ablated, may be sources of local tumor progression due to sublethal thermal injury. So we evaluate the treatment effect of radiofrequency-induced hyperthermia (RFH) combined with intra-tumoral chemotherapy for rabbit VX2 liver tumors and explore the underlying mechanism that drives local hyperthermia-enhanced chemotherapy. Methods: VX2 cell lines and rabbits with liver VX2 tumors were randomly allocated to four treatment groups including: (1) combination therapy of doxycycline (DOX) plus RFH (n=6); (2) DOX only; (3) RFH only (n=6); and (4) phosphate-buffered saline-treated control (n=6). Molecular biology methods were used to evaluate the treatment effect and explore the underlying mechanism both in vitro and in vivo. Results: RFH enhanced the chemotherapeutic effect of doxorubicin in VX2 cells and rabbit liver VX2 tumors resulting in higher apoptosis and lower cell viability. Fluorescence microscopy showed increased uptake of DOX in tumor cells in the combination therapy group. Conclusion: RFH enhanced the chemotherapeutic effect of DOX in VX2 tumors by promoting the uptake of DOX and the expression HSP70 in tumors.